2002
DOI: 10.1063/1.1494420
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of oligothiophene self-assembled monolayers on gold substrate

Abstract: Liner and nonlinear-optical properties of oligothiophenes self-assembled monolayers ͑SAM͒ are studied by optical second harmonic interference technique. Linear polarizability and first hyperpolarizability as functions of the number of thiophene rings are calculated using a self-consistent approach for linear and nonlinear optical properties. Both of these dependencies can be described by a power law; a nonzero first hyperpolarizability points to the asymmetry of delocalized electron system that might be due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…38,39,40 However, researchers have long realized that the crucial issues in the quantitative interface studies with the SHG and SFG are on how to describe the macroscopic dielectric constant of the molecularly thin layer and how to calculate the anisotropic two dimensional microscopic local field effect. 21,25,41,42,43,44,45,46,47,48,49,50,51,52,53 It has been well demonstrated that in majority cases the calculation of the molecular orientation is quite sensitive to the values used for these two factors. 21,25,42,51,52 In the currently accepted models of the nonlinear optics of interface, 4,34,41,53,54,55 the nonlinear radiation was treated as the result of an infinitesimally thin polarization sheet layer, and as the starting pint a macroscopic dielectric constant was assigned to this thin layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39,40 However, researchers have long realized that the crucial issues in the quantitative interface studies with the SHG and SFG are on how to describe the macroscopic dielectric constant of the molecularly thin layer and how to calculate the anisotropic two dimensional microscopic local field effect. 21,25,41,42,43,44,45,46,47,48,49,50,51,52,53 It has been well demonstrated that in majority cases the calculation of the molecular orientation is quite sensitive to the values used for these two factors. 21,25,42,51,52 In the currently accepted models of the nonlinear optics of interface, 4,34,41,53,54,55 the nonlinear radiation was treated as the result of an infinitesimally thin polarization sheet layer, and as the starting pint a macroscopic dielectric constant was assigned to this thin layer.…”
Section: Introductionmentioning
confidence: 99%
“…26,59,60,61 There have been a few experimental and empirical theory studies on the SHG data from the interfacial monolayer, using different parameters of the macroscopic three layer model plus the microscopic local field factors. 43,44,45,46,47,48,49,50,51,62,63,64 In dealing with the macroscopic dielectric constant, generally one of the two bulk phase values were used, reducing the macroscopic problem to the same as the so-called two phase model. 65,66 However, because the two phase model does not consider the different microscopic properties of the surface molecular layer, it can only phenomenologically describe the surface SHG process, and it generally fails to qualitatively explain the observed differences in the SHG measurement.…”
Section: Introductionmentioning
confidence: 99%
“…43,44,45,46,47,48,49,50,51,81 Therefore, we shall neglect the image induced dipole term in the followed treatment.…”
Section: 89mentioning
confidence: 99%
“…26,59,60,61 There have been a few experimental and empirical theory studies on the SHG data from the interfacial monolayer, using different parameters of the macroscopic three layer model plus the microscopic local field factors. 43,44,45,46,47,48,49,50,51,62,63,64 In dealing with the macroscopic dielectric constant, generally one of the two bulk phase values were used, reducing the macroscopic problem to the same as the so-called two phase model.…”
Section: 25mentioning
confidence: 99%
See 1 more Smart Citation